Labour mobility, industry evolution and social networks: a co-evolutionary model - Mamede, Ricardo (2012)
This paper presents a model that was built in order to analyse the interdependencies between labour market dynamics and the evolution of industries’ structure, in situations where interpersonal links among workers influence individuals’ job decisions. The model was inspired by the case of industries that rely heavily on highly skilled labour and in which problems of incomplete information abound. The causal mechanisms here proposed constitute an alternative explanation for a number of well-known regularities of industry evolution and of labour mobility, being arguably more suitable to the analysis of those industries than the formal models available in the literature.